Selective cytotoxicity of intense nanosecond-duration electric pulses in mammalian cells - Ibey, Bennett L.; Pakhomov, Andrei G.; Gregory, Betsy W.; Khorokhorina, Vera A.; Roth, Caleb C.; Rassokhin, Mikhail A.; Bernhard, Joshua A.; Wilmink, Gerald J.; Pakhomova, Olga N. (Biochimica et biophysica acta, 2010)
Nanosecond electric pulses (EP) disrupt cell membrane and organelles and cause cell death in a manner different from the conventional irreversible electroporation. We explored the cytotoxic effect of 10-ns EP (quantitation, mechanisms, efficiency, and specificity) in comparison with 300-ns, 1.8- and 9-μs EP. Effects in Jurkat and U937 cells were characterized by survival assays, DNA electrophoresis and flow cytometry. 10-ns EP caused apoptotic or necrotic death within 2-20 h. Survival (S, %) followed the absorbed dose (D, J/g) as: S=alphaD((-K)), where coefficients K and alpha determined the slope and the "shoulder" of the survival curve. K was similar in all groups, whereas alpha was cell type- and pulse duration-dependent. Long pulses caused immediate propidium uptake and phosphatidylserine (PS) externalization, whereas 10-ns pulses caused PS externalization only. 1.8- and 9-μs EP cause cell death efficiently and indiscriminately (LD₅₀ 1-3 J/g in both cell lines); 10-ns EP are less efficient, but very selective (LD₅₀ 50-80 J/g for Jurkat and 400-500 J/g for U937); 300-ns EP show intermediate effects. Shorter EP open propidium-impermeable, small membrane pores ("nanopores"), triggering different cell death mechanisms. Nanosecond EP can selectively target certain cells in medical applications like tumor ablation.